Topdressing nitrogen fertilization associated with trinexapac-ethyl on industrial quality of oat grains - Bizzarri Bazzo, José Henrique; Riede, Carlos Roberto; Antunes Arruda, Klever Márcio; Zucareli, Claudemir; de Batista Fonseca, Inês Cristina (Revista Ceres, 2025)
Nitrogen fertilization, besides increasing productivity, can favor the production of well-formed, large, and heavy grains, which are traits valued by the oat processing industry. However, high nitrogen (N) doses may lead to plant lodging, which could be solved by using growth retardant. This study aimed to evaluate the industrial quality of white oat grains cultivated under different nitrogen doses and associated with the growth retardant trinexapac-ethyl in two growing environments. Experiments were conducted in Londrina and Mauá da Serra, PR, Brazil, using the cultivar IPR Afrodite in a randomized block design in a 4 × 2 factorial scheme and four replications. Treatments consisted of four topdressing N doses (0, 30, 60, and 90 kg ha-1) and the application or not of growth retardant. Thousand-grain weight, hectoliter weight, grain index greater than two millimeters, peeling index, and industrial grain yield were evaluated. The effect of N fertilization and growth retardant on the industrial quality of white oat grains depends on the characteristics of the growing environment. The trinexapac-ethyl application reduces grain quality in Londrina and Mauá da Serra. However, the industrial quality of grains is high in both growing environments when the growth retardant is associated with nitrogen doses.